La Vierge sans âge. Mythes et rites, images et parentés - Salvatore D’Onofrio (Images Re-Vues)
This article studies the status of images concerning the most important parental configuration of the Christian horizon: the relationship between the Virgin and her Son. The iconographic tradition, especially Byzantine, illustrated the different facets of this relationship, including those generated by the belief in the virgin birth and the Trinity. It also helped to stabilize the myths of the gospels (canonical and apocryphal) which promoted it. Strictly mixed with the liturgical word and popular rituals, the images help to understand better the symbolic work that underlies reversed filiation (visible for example in the Dormitio virginis). The sacred marriage is depicted in numerous images of the Assumption and in meetings between the Easter statues of the Risen Christ and his rejuvenated mother.